Transitional Experiences from Clinical Nurse Experts to Novice Nurse Lecturers in the University for Local Development in Thailand: A Phenomenological Study - Wongpimoln, Boonyada; Pholputta, Ladda; Ngernthaisong, Chaowarit; Sarnkhaowkhom, Chawapon (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Nurse lecturers play a vital role in producing professional and competent nurses through teaching and practicing in universities. It is challenging for clinical nurse experts to adapt to being nurse lecturers in the university for local development. Exploring this transitional experience is essential to learn how nurses adapt themselves to their new roles.Purpose: This study aimed to describe the transitional experiences from clinical nurse experts to novice nurse lecturers in the context of the university for local development.Methods: The Heideggerian hermeneutic phenomenology was used as a research methodology. The purposive sampling was utilized to select eight novice nurse lecturers as participants. Data were ethically collected using in-depth interviews, observations, field records, and voice recordings. The collected data were then transcribed verbatim, and a thematic analysis based on van Manen’s method was applied for data analysis.Results: The findings showed five major themes and four sub-themes, including: (1) Reasons for becoming a nurse lecturer in the university for local development, consisting of having a successful career and desiring to serve the community in their hometown; (2) Learning to work by relying on themselves; (3) Learning and teaching through an offered service for local development; (4) Seeking support, consisting of focusing on students as moral support and asking for recommendations from colleagues; and (5) Confidently moving forward.Conclusion: Understanding transitional experience from clinical nurse experts to novice nurse lecturers in the university for local development is very challenging, especially in managing difficulties in the role transition. It is expected that nursing schools provide an effective orientation and mentorship programs to help nurse lecturers promote their role transition efficiently.